Answer:
![a=\displaystyle(1)/(2)+\displaystyle(√(3))/(2)i\\\\a=\displaystyle(1)/(2)-\displaystyle(√(3))/(2)i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ryigv1w7xi9udjzag8mm2avqsmd644hlki.png)
![b=\displaystyle(1)/(2)+\displaystyle(√(3))/(2)i\\\\b=\displaystyle(1)/(2)-\displaystyle(√(3))/(2)i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/38ymddu20jhzngowouhrz493f2y6ndkigo.png)
Explanation:
Recall that
so
we have then
Isolating b in the second equation we get
b = 1-a
Replace this value in the first equation
Solving the quadratic equation we get two possible solutions for a
Replacing these values in b=1-a, we get two possible solutions for b
![b=\displaystyle(1)/(2)+\displaystyle(√(3))/(2)i\\\\b=\displaystyle(1)/(2)-\displaystyle(√(3))/(2)i](https://img.qammunity.org/2020/formulas/mathematics/middle-school/38ymddu20jhzngowouhrz493f2y6ndkigo.png)